The Effectiveness of Woolwich Massage and Rolling (BACK) Massage on Breast Milk Quantity - Nining Rohniyati; Lili Farlikhatun (Global Health Science Group, 2023)
Inadequate breast milk production can cause breastfeeding to stop before the baby is 6 months old. One effort that can be done to stimulate the hormones prolactin and oxytocin in the mother. There are 2 non-pharmacological ways to maximize the production of prolactin and oxytocin, namely Woolwich massage and rolling back massage. The purpose of this study was to look at the effectiveness of Woolwich massage and rolling back on the expenditure or quantity of breast milk. This research is a type of intervention research with experimental quasy design. The location used for this study is in the working area of the midwife clinic Rahmawati Serang – Banten in June – July 2023. The samples used in this study were 15 people as the woolwich group and 15 postpartum mothers as the rolling back group. The bivariate analysis used in this study was to determine whether there was a relationship with the Chi-Square test. In the rolling massage group there were 10 respondents (33.3%) and not much different in the Woolwich massage group also the majority of breast milk volume >500 ml there were 11 (36.7%) respondents. Analysis results (OR: 0.73; 95% Confident Interval 0.15 – 3.49; p value 0.690).